Verbal Group Complexes Application In Palang Tamak Text Systemic Functional Linguistics Perspective - I Ketut Suardana (International Journal of Linguistics and Discourse Analytics, 2021)
Pan Balang Tamak text is one of Balinese narrative texts developing in Balinese communities. This text contains very deep moral value that is very useful for communities to achieve happiness in the world. The moral values embed in the clauses constructing the text in metaphorical meaning. Many clauses constructing the text contain verbal group complexes in which describe kinds of actions done by the participants. This paper analyzes the application of verbal group complexes in Pan Balang Tamak text written by Suptra (2014). The theory used to analyze the verbal group complexes is the theory of group complex from Systemic Functional Linguistics from Halliday (2014). The paper used qualitative research, namely by the theory approach, the technique used is based on syntagmatic and paradigmatic based on field, tenor, mode. The result of the research suggested that both verbal group complexes in paratactic and in hypotactic were found in the text. Paratactic can be found in the way of the communities respect their bad behavior and the real condition happening to all animal living in the forest. The hypotactic were found the clauses which contain the effort to trap Pan Balang Tamak and the advantages obtained by Pan Balang Tamak from the efforts which be trap Pan Balang Tamak. Projection verb can be found in verbal process in which mean proposal, namely, the willing to trap Pan Balang Tamak